Edukacja jako nośnik doświadczenia pedagogicznego w kontekście kreacji podmiotu pedagogicznego. Próba ustanowienia postpedagogiki - Dembiński, Mariusz (Studia Edukacyjne, 2017)
In this article, I want to propose post-pedagogy – a knowledge which is independent of social science. For this purpose, I use the content of pedagogy to create a sense of pedagogical experience and to definethe model of the pedagogical subject. Creation should be carried out using the principles of thinking and pedagogical activities, transforming information about the education system in educational activities, which comprise upbringing and training.